Reading Tealeaves On The Potential Impact of The Privatization of Tea Estates In Rwanda - Essama-Nssah, Boniface, 1949- 1949- (The World Bank, 2008)
The Poverty Reduction Strategy of the Government of Rwanda seeks to unlock the growth and poverty reduction potential of the tea sector through the privatization of tea estates. This paper uses the logic of causal inference and data from the 2004 Quantitative Baseline Survey of the tea sector to assess the potential impact of the privatization program. This entails a normalized comparison of productivity outcomes to account for household heterogeneity in terms of observable and non-observable determinants of these outcomes. The paper also compares living standards between tea and non-tea households. Three main findings emerge from the analysis. Productivity outcomes are generally better in the private sector than in the public sector. Male-headed households outperform female-headed households along all dimensions considered here. And tea households tend to be better off than non-tea households